OPTIMIZATION OF THE PREVENTION OF DENTAL DISEASES IN MECHANICAL ENGINEERING WORKERS - Nizomiddin N. Sadriev (Central Asian Journal of Medicine, 2024)
It is known that a complex of occupational factors contributes to the development of chronic diseases of the oral cavity, such as hypertrophy of the palatine tonsils, subatrophic diseases of the oral mucosa, inflammation of periodontal tissues, carious and non-carious lesions of the hard tissues of the teeth. The study of the epidemiology of dental diseases conducted in many countries of the world indicates significant differences in the prevalence and intensity of dental caries, periodontal diseases and oral mucosa, and the determining role of natural, social, domestic, cultural, as well as occupational and industrial factors in the development of these processes.